Seroprevalence of chikungunya fever virus and O’nyong Nyong fever virus among febrile patients visiting selected hospitals in 2011-2012 Trans Nzoia County, Kenya - Kamau, Kevin K.; Magoma, Gabriel; Kwallah, Allan Ole; Syengo, Charles K.; Mwau, Matilu (International Journal of Research in Medical Sciences, 2018)
Background: Chikungunya virus (CHIKV) is an alphavirus in the Semliki Forest complex, and is most closely related to O’Nyong Nyong virus (ONNV). CHIKV and ONNV are mosquito-borne alphaviruses endemic in East Africa that cause acute febrile illness and arthralgia. The objectives of this study were to measure seroprevalence of CHIKV and ONNV in selected health facilities in Western Kenya and link it to demographics and other risk factors. Methods: The study design was cross sectional in selected health facilities. We tested for anti-CHIKV antibodies using In-house Indirect IgG Enzyme Linked Immunosorbent Assay (ELISA) and In-house IgM Capture ELISA and confirmed with Focus Reduction Neutralization Test (FRNT) for specific alphavirus neutralizing antibodies against CHIKV or ONNV. Mean, median and standard deviation were used to summarize the data. Comparisons of means and medians were done using Student’s t test. Prevalence rates were determined using descriptive statistics (e.g. proportions, rates). Results: From the 382 samples that were successfully collected, 114 (29.84%) had anti-CHIKV antibodies by the ELISA test. Of these, 27 (7.1%) had CHIKV-specific neutralizing antibodies and 5 (1.3%) had ONNV-specific neutralizing antibodies. Age was significantly associated with seropositivity (OR=1.03; P=0.015, 95% C.I 1.01-1.06). Males were less likely to be seropositive (OR=0.67; P=0.358, 95% C.I 0.27-1.52). Risk factors associated with seropositivity included collecting firewood (OR=2.73 95% 1.13- 6.41) and walls with holes and cracks (OR=0.23 95% C.I 0.04 -0.86). Conclusions: Both CHIKV and ONNV infections were confirmed in the participants’ more so in women and adults, demonstrating undocumented and ongoing transmission in Western Kenya. In 2011 and 2012 CHIKV and ONNV contributed 8.4% of fevers presented in the three selected health facilities in Western Kenya.